2008
DOI: 10.1111/j.1750-3639.2008.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Orthotopic Human Glioma Models and Its Relevance for the Study of Anti‐glioma Therapy

Abstract: Most human gliomas are characterized by diffuse infiltrative growth in the brain parenchyma. Partly because of this characteristic growth pattern, gliomas are notorious for their poor response to current therapies. Many animal models for human gliomas, however, do not display this diffuse infiltrative growth pattern. Furthermore, there is a need for glioma models that represent adequate genocopies of different subsets of human gliomas (e.g., oligodendrogliomas). Here, we assessed the intracerebral growth patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
108
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 44 publications
2
108
0
Order By: Relevance
“…[5][6][7][8][9][10][11]29,30 Although gliomas are certainly at the extreme end of a spectrum with respect to infiltrative growth, it was recently shown that targeting of the angiogenic pathway also in subcutaneous xenografts leads to enhanced invasive growth and metastases. 31,32 Such adverse effects are not expected to occur when directing therapy against the existing tumor vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[5][6][7][8][9][10][11]29,30 Although gliomas are certainly at the extreme end of a spectrum with respect to infiltrative growth, it was recently shown that targeting of the angiogenic pathway also in subcutaneous xenografts leads to enhanced invasive growth and metastases. 31,32 Such adverse effects are not expected to occur when directing therapy against the existing tumor vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…28 In vivo Selection of Tumor Vessel Binding Nanobodies via Biopanning of Phage Display Libraries To grow intracerebral E98 and E434 tumors, Balb/c nude mice were transcranially injected with the glioblastoma xenograft line E98 (n ¼ 2) or the oligodendroglioma line E434 (n ¼ 2) essentially as described earlier. 11 In short, a mouse carrying a subcutaneous E98 tumor and one carrying a cerebral E434 xenograft were killed. The tumors were sterile removed, minced to small pieces and filtered through a 70-mm mesh nylon filter.…”
Section: Llama Phage Display Library Constructionmentioning
confidence: 99%
See 3 more Smart Citations